Continuous co-generation of biohydrogen and biomethane through two-stage anaerobic digestion of hydrothermally pretreated food waste. (15th September 2022) - Ding, Lingkan; Cheng, Jun; Qiao, Dan; Li, Hui; Zhang, Ze
Graphical abstract: Highlights: Hydrothermal pretreatment (HTP) at 140 °C for 20 min was applied to food waste (FW). Long-term continuous two-stage H2  + CH4 production of HTP-treated FW was validated. Higher H2 (3.8%) and CH4 (167.7%) yields were achieved than that using untreated FW. Microbial analyses revealed less proteolytic bacteria & more versatile methanogens. A 66.7% increase in treatment capacity was achieved with a balanced energy yield. Abstract: Increasing accumulation of food waste (FW) exerts pressure on resource conservation and environmental protection, while conventional anaerobic digestion (AD) of raw FW for bioenergy recovery and waste minimization often encounters limitations such as fast acidification and process failure. Herein, mild hydrothermal pretreatment (HTP: 140 °C, 20 min) of raw FW was employed to advance subsequent AD performances in a long-term continuous mode. With a decreased overall hydraulic retention time (HRT) from 30 to 18 days, the two-stage system digesting HTP-treated FW maintained very stable and robust biohydrogen (38.1 mL/gVS) and biomethane (439.6 mL/gVS) co-production, whereas both the two-stage system digesting raw FW and the one-stage system digesting HTP-treated FW exhibited deteriorating trends with significantly lower energy yields by 61.1% and 28.1%, respectively. Microbial community analyses revealed the less involvement of carbohydrate-fermenting and proteolytic microbes in the second-stage biomethane reactors as a result of the enhanced hydrolysis and acidogenesis of FW through HTP and first-stage biohydrogen fermentation. A proximate energy balance assessment indicated that the energy gain of increased biogas generation offset the extra heat requirement for the HTP of FW, while a significant treatment capacity enhancement of 66.7% was achieved given the HRT reduction from 30 to 18 days through this integrated system.